Mediação interdisciplinar e sua integração com o poder judiciário de Pernambuco - Cavalcanti, Fernanda Daniele Resende (2009)
This study aims to analise the interdisciplinar mediation system under the new science paradigm, however, not as an alternative or same break to use the traditional litigation system, but trying to integrate or connect one to another, as one more function of Welfare state. The work starts from a historical account of mediation throghout the world, with enphasis in the countries which have more influence over Brazil´s own mediation system construction. New science paradigms are discussed by their dimensions of complexity, instability and intersubjectivity, which validate the need of integration between legal and mediation systems and, at last, the mediation is analysed into its more relevants aspects, that is, the power of management of conflicts, legal nature, interdiciplinarity and mediator´s interventions. Brazilian legislative moviment towards the legalization of mediation is also presented, as well as the description of mediation use in Pernambuco State by the Conciliation, Mediation and Arbitration Center of Recife. The research method was based upon the reading of a vaste bibliography about the subject at the Law Science framework, helped by same other disciplines, as well as by a case study which was built after the analysis of 1,481 legal agreements that took place in the period between June, 2008 and May, 2009 at CMA-Recife. The results suffered a statistic evaluation and acchieved their aims, specially by the identification of an adequate way for peaceful and kind conflicts resolution that should be integrated to the traditional legal system